Language and Thinking Relationships in Ketemuq-Meretuq Culture in Batu Samban Village - Adha, Isna Dia'ul; Saleh, Mustakim (Journal of Advance in Language, Literature, and Education, 2025)
This article aims to add to the reader's understanding of culture in a society, where the inherited doctrine of belief has become an unconsciously ingrained belief in Sasak society. The Sasak community's belief in the existence of ketemuq in the era of generation Z has not completely disappeared. Some people argue that this belief is included in the myth but not a few people still carry out the process. This article was created to illustrate that a small habit in a society can have a good or bad impact on that society, the language in ketemuq-meretuq gives suggestions in the minds of people who believe in it. Belief can be a suggestion for a person's mentality, and have an impact on life.